A study on assessment of safe injection practices among internees in government general hospital, Kakinada, Andhra Pradesh, India - Peethala, Sujatha; Garapati, Sridevi (International Journal Of Community Medicine And Public Health, 2017)
Background: Injections are commonly used in healthcare settings for the prevention, diagnosis, and treatment of various illnesses. Unsafe injection practices put patients and healthcare providers at risk of infectious and non-infectious adverse events. Safe injection practices are part of standard precautions and are aimed at maintaining basic levels of patient safety and provider protections. Objectives of this study were to assess the knowledge and observe safety practices while giving the injections. Methods: A cross-sectional study conducted among 200 internees in Government General Hospital, Kakinada, Andhra Pradesh in the months of January and February 2010. Data was obtained by semi- structured questionnaire; analyzed by using SPSS software version16.0 at p<0.05 significance level. Results: In the present study, knowledge of internees was enquired into and practices were also observed in various aspects of injection safety. Knowledge on washing hands before giving injection was 64% but when it comes to practice, it was only 29%; knowledge on use of hub-cutter after giving injection was found to be 48% but in practice hub-cutter use was observed to be very less (5.5%); knowledge on safe disposal of used syringes was 42% but only 9.0% were practicing safe disposal. Similarly knowledge on use of color coded bags according to guidelines was 40.5% and in practice it was observed to be 14%. Conclusions: In the present study knowledge and practices on injection safety was found to be poor; dissemination of IEC, behavior change campaigns and continuing education on universal precautions and proper disposal of injection related waste was recommended.